PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA KONDISI KEDARURATAN PANDEMI COVID-19 - Baihaqi, Naufal; Geraldina, I.; Wijaya, S.Y. (Jurnal Akunida, 2021)
This study aims to determine the effect of capital structure on value in the emergency conditions of the covid-19 pandemic emergency in basic materials, consumer cyclicals, non-cyclical consumer, healthcare and industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research is a type of quantitative research using secondary data in the form of the company’s annual report. Fixed Effect Model (FEM) with panel data regression was used in this study using STATA version 16. Capital structure has no significant effect on firm value, the covid-19 pandemic is not able to moderate capital structure on firm value, while the control variable, namely firm size, has a significant negative effect. on firm value and profitability have a significant positive effect on firm value.